Setting optimal rents for apartment firms - Wang, Jian (Henry Stewart Talks, 2009)
Apartment industry represents a new frontier for pricing and revenue management, An introduction to the traditional rental settings, Analysis in the form of comparison between hotel and apartment firms, Step-by-step methodology of setting optimal rents, A real case study